2015
DOI: 10.1007/s10570-014-0535-5
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of cellulose content, crystallinity, and lateral packing in Gossypium hirsutum and Gossypium barbadense cotton fibers using sum frequency generation, infrared and Raman spectroscopy, and X-ray diffraction

Abstract: The mesoscale packing and crystal structure of cellulose microfibrils as well as temporal changes in cell wall composition and hydration during the development of cotton fibers from two species, Gossypium hirsutum and G. barbadense were studied using vibrational sum frequency generation (SFG), attenuated total refection infrared (ATR-IR), Fourier transform Raman (FT-Raman) spectroscopy and X-ray diffraction (XRD). The developmental stages analyzed (13-60 days post anthesis) included primary wall synthesis, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 49 publications
5
34
0
Order By: Relevance
“…In a previous study by Wang et al [50], it was also found that a decrease in the SFG peak intensity ratio (CH 2 /OH) correlated with fibrillation of the cellulose elementary fibrils in pretreated biomass samples as observed by TEM. A similar correlation between the reduced CH 2 /OH ratio and lower packing density of cellulose elementary fibrils has been observed for plant cell walls [49, 51].
Fig.
…”
Section: Resultssupporting
confidence: 81%
“…In a previous study by Wang et al [50], it was also found that a decrease in the SFG peak intensity ratio (CH 2 /OH) correlated with fibrillation of the cellulose elementary fibrils in pretreated biomass samples as observed by TEM. A similar correlation between the reduced CH 2 /OH ratio and lower packing density of cellulose elementary fibrils has been observed for plant cell walls [49, 51].
Fig.
…”
Section: Resultssupporting
confidence: 81%
“…In particular, the overall SFG intensity, the alkyl peak shape, and the alkyl/hydroxyl intensity ratio have been shown to depend on the mesoscale assembly of cellulose, such as the lateral packing and net directionality of microfibrils (Lee et al, 2014). Recent work shows that SFG can detect the difference in arrangement of cellulose microfibrils between primary and secondary cell walls (Lee et al, 2014, 2015a). On the basis of the CH/OH relative intensity in SFG, it was suggested that over the SFG coherence length, primary cell walls have a lower degree of antiparallel orientation of cellulose microfibrils (Lee et al, 2014).…”
Section: Cellulose Microfibril Size and Organizationmentioning
confidence: 99%
“…For example, the appearance of FT-IR bands at 1733 cm −1 (C=O stretching originating from esters or amides) and 1534 cm −1 (NH 2 deformation corresponding to proteins or amino acids) reflects the presence of such non-cellulosic components as esters and proteins in cotton fibers [ 11 , 13 ]. Among these techniques, the ATR FT-IR spectroscopy method has evolved as an important alternative to examine cotton fiber development, because it requires minimal sample preparation by ATR sampling on a small bundle of cotton fibers as little as 0.5 mg, permits routine analysis rapidly and non-destructively, and is easy to operate [ 10 , 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different spectral interpretation approaches have been applied to acquire useful information from FT-IR measurement. It includes the direct use of 1-band intensity, the estimation of 2- or 3-band intensity ratios, and the implementation of a chemometrical or multivariate tool known as principal component analysis (PCA) [ 10 , 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The results have indicated that both simple algorithms and PCA patterns can be used to monitor the transition from PCW to SCW biosyntheses in cotton fibers.…”
Section: Introductionmentioning
confidence: 99%